Augmentation of the Sympathetic Skin Response after Electrical Train Stimuli - Emmer, Alexander; Mangalo, Sarah; Kornhuber, Malte E. (Frontiers in Neurology, 2012)
It is well known that the size of the SSR (sympathetic skin response) depends on the stimulus strength. In the present investigation train stimuli (TS) were employed to study the behaviour of the SSR when recruited above the usual level. The SSR was obtained in healthy human subjects over the palm of the hand after supramaximal single stimuli (SS) and trains-of-3 (TS; interstimulus-interval 3 ms) over the ipsilateral superficial radial nerve in 15 healthy volunteers. Ipsilateral to the stimulus site SSR amplitudes were 5.7±5.3mV (SS) and 7.7±5.9mV (TS; p<0.001), and contralateral 6.3±6.3mV (SS) and 7.2±4.9mV (TS; not significant). The relative gain in amplitude after TS vs. SS was negatively correlated with the SSR amplitude after SS ipsilateral (p<0.0005) and contralateral to the stimulus site (p<0.01). The increase in SSR amplitudes after TS compared with SS is in line with temporal summation of the excitatory synaptic input in neurons generating the SSR. Driving the SSR with TS is of possible relevance for the investigation of disorders of the peripheral or central autonomic nervous system.